Effect of Fermentation Time on Physiochemical Properties of Kombucha Produced from Different Teas and Fruits: Comparative Study - Siying Li; Yang Zhang; Jingrong Gao; Tong Li; Huizhen Li; Adele Mastroyannis; Shan He; Abdul Rahaman; Kun Chang (Journal of Food Quality)
This study aimed to investigate the impact of fermentation time on antioxidative activities and phenolic composition and sensory quality of kombucha fermented from different teas (green, black, and oolong) and fruits (grape, dragon, and guava). Results: the highest antioxidative activity was observed in kombucha from green tea and grapefruit fermented for 6-7 days at 25–30°C and 48 h at 37°C, respectively. Further analysis revealed that the antioxidative activity of grape kombucha was significantly improved due to an increase in polyphenols’ concentration as compared to original green tea kombucha. Furthermore, the sensory evaluation of grape kombucha suggested that grape-flavoured kombucha is more acceptable by the young-aged group. In conclusion, this study provides a potential and promising method for the first time to produce fruit-flavoured kombucha with increased bioactive compounds in very short fermentation time (48 h) which could fulfil the nutritional requirement for human health.